Development of a Crop Growth Detecting System. Issue 16 (2016) - Liu, Haojie; Sun, Hong; Mao, Bohui; Li, Minzan; Zhang, Man; Zhang, Qin
Abstract: In order to monitor crop growth in real-time, a new crop detection system was developed to measure spectral reflectance of crop canopy, which was based on ground-based remote sensing and wireless sensor network (WSN) technology. The system mainly contains two parts: the controlling unit and the measurement unit. The controlling unit was a PDA in which was embedded a ZigBee wireless communication module. And as the coordinator of the whole wireless sensor network, the controller was used to receive, display, store and process all the data from different optical sensor nodes. The measurement unit, including four optical channels, was designed to collect, amplify and transmit the optical signals. The sensor node can measure the spectral reflectance at the wavelength of 550, 650, 766 and 850 nm. Calibration test was conducted. The result showed a good performance in terms of the wireless transmission ability and the sensor measurement precision. Field experiments were also conducted in a winter wheat experimental field, and the NDVI values calculated from the spectral data can reflect different nitrogen stress and the chlorophyll content of winter wheat. The result shows that the system can meet the demands of practical use in the field and has potential for field application.